A methodology for recovering cassava plants from shoot tips maintained in liquid nitrogen - Escobar Pérez, Roosevelt H.; Mafla, G.; Roca, W. (Springer, 1997)
Shoot tips of in vitro-grown plantlets of cassava (Manihot esculenta Crantz), representing a wide range of germplasm, were cryopreserved as follows: precultured for 3 days, cryoprotected and dehydrated for 1 h, then frozen in liquid nitrogen using a six-step protocol. After 3 h in liquid nitrogen, the shoot tips were removed, rapidly warmed, and recultured sequentially in three recovery media. After 2 weeks, the regeneration of frozen shoot tips was completed. Genotypes with a low response were identified. Their response was attributed to the effects of pre- and post-freezing steps. Refining the methodology led to a consistent 50-70 percent plant recovery. (RA)